Money supply and its effect on unemployment An analytical study in the Iraqi economy for the period (2004-2019) - Noori Alhamdany, Saad; Khalifa Obaid, Muhannad (International Journal of Psychosocial Rehabilitation, 2020)
The research paper indicates an effect statement and analysis of the relationship between the money supply and unemployment to detect the effects that the money supply has on unemployment. The research assumed that there was an effect of the money supply on unemployment, as proven by standard tests. The dependent variable of unemployment and the results of the research revealed an inverse relationship between the variable of money supply and unemployment, and through this relationship, the monetary authority can influence these economic variables to achieve economic stability.